Enhanced Fluorescent Assignment of Protein Aggregates by an Oligothiophene–Porphyrin‐Based Amyloid Ligand. Issue 9 (7th March 2013) - Arja, Katriann; Sjölander, Daniel; Åslund, Alma; Prokop, Stefan; Heppner, Frank L.; Konradsson, Peter; Lindgren, Mikael; Hammarström, Per; Åslund, K. O. Andreas; Nilsson, K. Peter R.; Tang, B. Z.; Liu, B.
Abstract Fluorescent probes identifying protein aggregates are of great interest, as deposition of aggregated proteins is associated with many devastating diseases. Here, we report that a fluorescent amyloid ligand composed of two distinct molecular moieties, an amyloidophilic pentameric oligothiophene and a porphyrin, can be utilized for spectral and lifetime imaging assessment of recombinant Aβ 1‐42 amyloid fibrils and Aβ deposits in brain tissue sections from a transgenic mouse model with Alzheimer's disease pathology. The enhanced spectral range and distinct lifetime diversity of this novel oligothiophene–porphyrin‐based ligand allow a more precise assessment of heterogeneous amyloid morphology compared with the corresponding oligothiophene dye.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>